Policy-Driven Determinants of Foreign Direct Investment in Finland’s Hydrogen Sector - Klemola, Roope (My University, 2026)
This thesis examines how public policies and regulatory frameworks affect the flow of FDI into the green hydrogen sector in Finland. As the European Union is accelerating the transition to green energy sources, green hydrogen has emerged as one of the most relevant industries to tackle emissions produced by hard-to-abate sectors. The EU and its member states have implemented regulations to secure demand and reduce the riskiness caused by high capital intensity of investments and the perceived high asset specificity. Given the limited domestic ability to finance these investments, investments flowing from abroad serve as key tools to achieve both national and EU-level targets. The thesis aims to address the main research question by analysing the following factors: the role of formal regulatory structures in shaping FDI flows in general, how EU and Finnish national-level legislation shapes financial feasibility and risk for foreign actors, and what location advantages the current regulatory environment creates for Finland as a host country. The thesis integrates Dunning’s OLI paradigm, Williamson’s Transaction Cost Economics, and Scott’s Institutional Theory into a single theoretical framework. The analysis relies on secondary data from, for example, EU and Finnish legislation, industry reports, and existing academic literature. Main outcomes of the analysis find that high asset specificity and large upfront capital requirements contribute to the perceived high-risk profile, which would deter FDI without government involvement. Examples of this government involvement include risk mitigation with EU’s RED III directive and fiscal incentives with Finnish national-level legislation such as Act 148/2025. The analysis also introduces the contradictory role of legislation, which not only mitigates but also introduces new transactional costs. The thesis concludes that Finland’s competitive location advantages originate from the combination of competitive resources, such as low wholesale energy prices, and proactive institutional signalling. Regulatory frameworks do not only reduce risks but help to manufacture a baseline for financial feasibility. By creating this baseline, the natural strengths of Finland begin to function as key location advantages to attract foreign capital.

Tässä kandidaatintutkielmassa tarkastellaan, miten julkiset toimet ja sääntelykehykset vaikuttavat ulkomaisten suorien sijoitusten virtaan vihreän vedyn alalle Suomessa. Euroopan unioni on kiihdyttänyt siirtymistä vihreisiin energialähteisiin viime vuosina. Tämän seurauksena vihreä vety on noussut yhdeksi merkittävimmistä toimialoista ilmastonmuutoksen torjumiseksi aloilla, joilla päästöjen vähentäminen on haastavaa. EU:n jäsenvaltiot ovat ottaneet käyttöön säännöksiä kysynnän luomiseksi sekä korkeiden transaktiokustannusten pienentämiseksi. Koska kotimainen kapasiteetti näiden investointien rahoittamiseen on rajallinen, ulkomailta tulevat investoinnit ovat keskeisiä välineitä sekä kansallisten että EU-tason tavoitteiden saavuttamisessa. Tutkielma tarkastelee kolmea alatutkimuskysymystä. Tutkielma tarkastelee yleisellä tasolla, miten sääntely vaikuttaa ulkomaisten suorien sijoitusten virtaan. Lisäksi se pyrkii vastaamaan siihen, miten EU:n ja Suomen kansallinen lainsäädäntö vaikuttaa ulkomaisten toimijoiden rahoituksen toteutettavuuteen ja riskeihin, sekä mitä sijaintietuja nykyinen sääntely-ympäristö luo Suomelle sijoituskohteena. Opinnäytetyö yhdistää Dunningin OLI-paradigman, Williamsonin transaktiokustannusteorian ja Scottin institutionaalisen teorian yhtenäiseksi teoreettiseksi viitekehykseksi. Analyysi perustuu toissijaisiin lähteisiin, esimerkiksi EU:n ja Suomen lainsäädäntöön, toimialaraportteihin ja akateemiseen kirjallisuuteen. Analyysin keskeiset päätelmät osoittavat, että alan korkeaan riskiprofiiliin vaikuttaa investointien vahva sitovuus paikkaan ja suuret alkuinvestointivaatimukset. Ilman valtion puuttumista nämä tekijät voivat estää ulkomaisia suoria sijoituksia. Esimerkkejä valtion osallistumisesta sijaintietujen luomiseen ovat EU:n RED III -direktiivi, joka luo kysyntää ja vähentää transaktiokustannuksia, sekä kansalliset verokannustimet, kuten laki 148/2025. Analyysissä käsitellään myös lainsäädännön ristiriitaista roolia, sillä se ei ainoastaan vähennä, vaan myös lisää uusia transaktiokustannuksia. Tutkielman johtopäätös on, että Suomen sijaintiedut syntyvät kilpailukykyisten resurssien, kuten alhaisten energian tukkuhintojen, ja ennakoivan institutionaalisen signalloinnin yhdistelmästä. Sääntelykehykset eivät ainoastaan vähennä riskejä, vaan auttavat luomaan perustan taloudelliselle toteutettavuudelle. Tämän perustan luomisen myötä Suomen luonnolliset vahvuudet alkavat toimia keskeisinä sijaintietuina ulkomaisen pääoman houkuttelemiseksi.
Keywords: Foreign Direct Investment; Institutions; Transaction Cost Economics; OLI Paradigm; Green Hydrogen; Location Advantages; Finland; Renewable Energy Policy; ulkomaiset suorat investoinnit; institutionaalinen teoria; transaktiokustannusteoria; OLIparadigma; vihreä vety; sijaintiedut; Suomi; energiapolitiikka; uusiutuvat energialähteet